Clínica e experiências literárias - Modolo, Luisa Tosi (2019)
This work is the result of an immersion in literary and philosophical works in order to follow between characters and concepts ways of being in the world. Driven by the expansion of horizons and displacements of this dive, we seek to let the pages that follow a writing that could contribute to the clinic. In a transdisciplinary way, we seek to enter perspectives that lead us to see the world in a different way from habits. We start from Gilles Deleuze's Proust and the Signs instigated by the concepts of sign and meaning and we continue through literary experiences groping the effects of these intercessions in the composition of more sensitive listening in the clinic. At the same time the writing process was unfolding in the construction of access ways to movements of meaning production more connected with life.